Nudge Evidence Briefing: A Proposal for Transferring Scientific Knowledge about Nudges - Gomes, Vinicius; Cunha, José Adson; Lima, Kássio; Moura, Hermano Perrelli (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
A nudge is a concept from Behavioral Economics and Psychology that refers to any small change or intervention designed to influence people's behavior predictably, without restricting their options or significantly altering their incentives. The research follows the Design Science Research methodology, introducing Nudge Evidence Briefing (NEB) to facilitate the understanding, access, application of academic findings on nudges for non-academic professionals, considering the gap between academic research on nudges and their practical application. Leveraging insights from the Evidence-Based Medicine framework, NEBs distill key findings from primary research into concise, accessible documents. Through a systematic review of the literature on nudge integration into software privacy and security, 12 primary studies were selected and the data extracted from them was formatted into NEBs. Participants, specialists and non-specialists, were invited to evaluate the NEB through online questionnaires. Feedback highlighted the clarity and structured format of the NEB, with particular praise for its ability to communicate complex scientific evidence in an accessible way. Overall, the NEB demonstrates significant promise in making nudge-related research more accessible and feasible. Ongoing refinements based on participant feedback will be crucial to realizing its full potential, contributing to the advancement of Human-Computer Interaction (HCI) and the practical application of nudges in professional environments. Future work will focus on evaluating the practical applicability of the NEB with non-academic professionals, exploring more reliable alternatives for generating NEBs through LLM, and developing a comprehensive repository of NEBs.